ELECTRICAL PROPERTIES AND THERMAL OXIDATIVE AGING STABILITY OF THE EVA/SILICA NANOCOMPOSITES USING EVAgMA COMPATIBILIZER - Tham, Do Quang; Chinh, Nguyen Thuy; Hoang, Thai (Vietnam Journal of Science and Technology, 2015)
The nanocomposites based on ethylene-vinyl acetate (EVA, 18% vinyl-acetate group) without and with 1wt.% EVAgAM (EVA graft anhydride maleic) and 2 – 5 wt.% nanosilica were prepared by melt mixing in a Haake intermixer at 160°C, roto speed of 50 rpm for 5 minutes. The volume resistivity, dielectric strength and dielectric loss of the nanocomposites were measured in according to ASTM D257, D149 and D150. The nanocomposites were placed in a Memmert hot air oven at 70°C for 168 hours to investigate thermal oxidation aging stability. The obtained results showed that nanosilica decreased volume resistivity and dielectric loss of the nanocomposites but it increased dielectric strength of EVA. The dielectric constant of the EVA/EVAgAM/silica nanocomposites is lower than that of EVA/silica nanocomposites was an evidence of dipolar interaction and hydrogen bonds between EVAgAM, EVA with nanosilica. The nanocomposites EVA/silica without and with EVAgAM were excellent electrical insulation materials (volume resistivity of 1013-1014 Ω.cm, dielectric loss of about 10-3 and dielectric strenngth of 22.1-26.7 kV/mm). The percentage of retention in mechanical properties of the nanocomposites EVA/EVAgAM/silica was higher than that of EVA. FTIR analyses of the nanocomposites before and after thermal oxidation aging showed that nanosilica and EVAgAM limited to degradate macromolecules of EVA.